Terpenoid-Rich Extract of Dillenia indica L. Bark Displays Antidiabetic Action in Insulin-Resistant C2C12 Cells and STZ-Induced Diabetic Mice by Attenuation of Oxidative Stress - Bo-Rim Song; Md Badrul Alam; Sang-Han Lee (MDPI AG, 2022)
Insulin resistance (IR) plays a key role in the pathogenesis and clinical outcome of patients with multiple diseases and diabetes. In this study, we examined the antidiabetic effects of a terpenoid-rich extract from Dillenia indica L. bark (TRDI) in palmitic acid-induced insulin resistance (PA-IR) in C2C12 myotube and a streptozotocin (STZ)-induced diabetic mice model and explored the possible underlying mechanism. TRDI showed potential DPPH- and ABTS-radical scavenging effects with a half-maximal inhibitory concentration (IC50) value of 9.76 ± 0.50 µg/mL and 17.47 ± 1.31 µg/mL, respectively. Furthermore, TRDI strongly mitigated α-glucosidase activity with an IC50 value of 3.03 ± 1.01 µg/mL, which was 92-fold higher than the positive control, acarbose (IC50 = 279.49 ± µg/mL). TRDI stimulated the insulin receptor substrarte-1 (INS-1), downregulated phosphoinositide-dependent kinase-1 (PDK1) and protein kinase B (Akt) in both normal and PA-IR C2C12 cells as well as in STZ-induced diabetic mice, enhanced glucose transporter 4 (GLUT4) translocation to the plasma membrane (PM), and increased glucose absorption. Furthermore, TRDI administration significantly reduced PA-induced reactive oxygen species (ROS) formation in C2C12 cells and increased the protein level of numerous antioxidant enzymes such as superoxide dismutase 1 (SOD1), catalase (CAT), glutathione peroxidase-1 (GPx-1) and thioredoxin reductase (TrxR) both in vitro and in vivo. Furthermore, TRDI facilitated nuclear factor erythroid 2 related factor 2 (Nrf2) nuclear translocation and increased HO-1 expression in PA-IR C2C12 cells and STZ-induced diabetic mice. However, for the inhibition of Nrf2, TRDI failed to resist the effects of IR. Thus, this study provides new evidence to support the use of TRDI for diabetes treatment.